Emprego da organocatálise como uma ferramenta da química verde em reações de adição conjugada : estudos visando a síntese de anéis indólicos - Feu, Karla Santos (Universidade Federal de São Carlos, 2012)
Organocatalysis has emerged as a powerful synthetic paradigm and has accelerated the development of new methods to make diverse chiral molecules. In addition, the small chiral organic molecules used to accelerate asymmetric reactions, In this regard L-proline and its derivatives have risen to gaining prominence. In the present work, we have designed and synthesized LProline derived organocatalysts 4 a-e bearing with the alkyl chain containing chalcogen moiety such as Sulfur & Oxygen and to evaluate their application as catalysts in enantioselective reactions. The synthesized catalysts 4a-e were then employed as organocatalysts in enantioselective conjugate addition of malonates to alfa, beta- unsaturated aldehydes in an environmentally benign approach. Several different reaction conditions were screened and enantiomeric excess upto 96% with good to excellent yields was achieved for the Michael adducts. The best result was achieved for organocatalyst 4b in aqueous reaction conditions. Exploiting the application of the synthesized Michael adducts 5a-i, we then decided for the synthesis of the biologically important substituted indole and it was successfully accomplished with good yields along with excellent ee.
Employment Organocatalysis as a tool of Green Chemistry in Conjugate Addition Reactions: Studies toward the Synthesis of Indole Rings
Keywords: Química orgânica; Organocatálise assimétrica; Adições conjugadas; Anéis indólicos; CIENCIAS EXATAS E DA TERRA::QUIMICA